Acid baking of spent lithium ion batteries for selective recovery of major metals: A two-step process - Meshram P.; Abhilash; Pandey B.D.; Mankhand T.R.; Deveci H. (My University, 2025)
The present work focuses on a two-step process for selective dissolution of metals from cathode active material of spent LIBs. Cathode powder baked at 300 °C using H2SO4 being subjected to first stage leaching with water extracted 78.6% Li, 80.4% Co in 60 min at 75 °C and 25% pulp density; recovery of Ni and Mn being low (<15%). In second stage, reductive leaching was performed using an acid mixture (H2SO4 and HNO3) with glucose solubilizing 67% Ni, 64.8% Mn in 45 min. The overall recovery of the metals was 93.2% Li, 90.52% Co, 82.8% Ni, 77.7% Mn. © 2016 The Korean Society of Industrial and Engineering Chemistry